2020
DOI: 10.3390/jcm9082478
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis Lowers the Cumulative Live Birth Rates in IVF by Decreasing the Number of Embryos but Not Their Quality

Abstract: Endometriosis and infertility are closely linked, but the underlying mechanisms are still poorly understood. This study aimed to evaluate the impact of endometriosis on in vitro fertilization (IVF) parameters, especially on embryo quality and IVF outcomes. A total of 1124 cycles with intracytoplasmic sperm injection were retrospectively evaluated, including 155 cycles with endometriosis and 969 cycles without endometriosis. Women with endometriosis had significantly lower ovarian reserve markers (AMH and AFC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 72 publications
(100 reference statements)
3
8
1
Order By: Relevance
“…The lower CLBR was partly attributed to the decreased number of available embryos and top-quality embryos in endometrioma women, which was consistent with the findings of Boucret et al. ( 22 ). Surgical intervention prior to IVF/ICSI treatment in endometrioma women improved oocyte maturation and fertilization rates, but not pregnancy outcomes, in either fresh embryo cycles or in frozen embryo transfer cycles.…”
Section: Discussionsupporting
confidence: 90%
“…The lower CLBR was partly attributed to the decreased number of available embryos and top-quality embryos in endometrioma women, which was consistent with the findings of Boucret et al. ( 22 ). Surgical intervention prior to IVF/ICSI treatment in endometrioma women improved oocyte maturation and fertilization rates, but not pregnancy outcomes, in either fresh embryo cycles or in frozen embryo transfer cycles.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the wide use of ART by endometriosis patients, endometriosis is highly associated with poor outcomes in in-vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI). Studies (5)(6)(7) have found that patients with endometriosis have lower clinical pregnancy rate, poorer ovarian response, lower egg retrieval rate, and higher gonadotropin demand than those with tubal infertility.…”
Section: Introductionmentioning
confidence: 99%
“…An increased incidence of arrested embryos in vitro corresponding to endometriosis parents has been long reported [ 29 ]. Endometriosis is an estrogen-dependent chronic inflammatory condition that affect reproductive potential of women resulting to infertility as oocytes retrieved from patients with endometriosis present with abnormal oocyte morphology and lower cytoplasmic mitochondrial content compared to women with other causes of infertility [ 224 , 225 , 226 ]. Endometriosis is a multi-factorial disease that may bear a genetic background.…”
Section: Resultsmentioning
confidence: 99%